Evaluation and optimization of progesterone release from intravaginal rings using response surface methodology - Helbling, Ignacio Marcelo (2015)
Response surface methodology was successfully used to study effect of formulation parameters on progesterone release from rings made of ethylene-vinyl acetate copolymers. Significant effects were estimated by an analyses of variance (ANOVA) and statistical model was constructed. Model predictions showed good agreement with experimental data. Results showed that mass of progesterone released can be enhanced by several strategies. In addition, model behavior was compared with previously validated model reported in the literature obtaining satisfactory results. The statistical model was also employed to optimize formulation parameters with the aim to reach release rate of about 3.545 ± 0.020 mg cm-2 days-1/2. Optimized prototype was tested in vitro. Results showed that optimized IVR has similar profiles than the commercial silicone device used as reference. Optimized ring would have several advantages over commercial one like lower initial and residual content of progesterone and the possibility of recycling rings after their usage avoiding incineration of used device (as in the case of silicone commercial device). Pharmacokinetics studies must be done to corroborate in vivo performance of optimized IVRs made of EVA.